Fostering Students’ Speech Texts: A Thematic Progression Analysis on Senior High School Students’ Speeches - Rachma Choirunnisa; Seful Bahri (Universitas Islam Negeri Palopo, 2026)
This research explores the themes and thematic development in high school students’ speeches at a speech contest organized by one of Indonesia’s prominent English tutoring centers in 2024. The research method employed in this research was descriptive qualitative using Systematic Functional Linguistics. Data in this research were obtained by observing YouTube videos of the respective speech contest. The videos were transcribed in the form of written text. Four videos were selected randomly and coded as ST1, ST2, ST3, and ST4. The results indicated that the four speeches realized most types of themes, with topical themes occurring most frequently. This suggests that students tended to focus on the specified topics and maintain coherence between sentences. The zig-zag pattern was the most frequently used in thematic progress. This indicates that the speakers tended to elaborate on the topic in the text more clearly by utilizing various available information. This research provides teachers with insight into the importance of students’ knowledge of themes and thematic development in the construction of their speeches.